Penggunaan Model Pembelajaran Visual Auditori Kinestetik (VAK) Berbasis Sosiodrama Dalam Meningkatkan Hasil Belajar IPS : Penelitian Tindakan Kelas di Kelas VIII-4 SMP Negeri 277 Jakarta - Nusa Peninda Hakim; Dian Alfia Purwandari; Sujarwo Sujarwo (Jurnal Studi Guru dan Pembelajaran, 2020)
This study aims to obtain empirical data regarding the use of Sociodrama-Based Visual Auditory Kinesthetic learning models in improving students' social learning outcomes. This research was conducted on students of class VIII-4 at SMP Negeri 277 Jakarta from October to November 2019. The research method used was Classroom Action Research (CAR). The study uses 3 cycles, and from each cycle consists of four stages, namely: Action Planning, Action Implementation, Observation, and Reflection. Based on the results of research from learning outcomes have increased in each cycle, cycle one of 52.77% (19 students) gained learning outcomes above KKM 79, cycle two by 75% (27 students) reached values above KKM 79, and cycle three of 88% (32 students) achieved a score above KKM 79. Besides that, the Sociodrama-Based Visual Auditory Kinesthetic Learning Model was able to increase the activeness of students in the aspects of asking, answering, arguing and working together. Thus it can be concluded that the use of Sociodrama-Based Visual Auditory Kinesthetic learning model can improve students' social studies learning outcomes and can increase student activity. So students can get better social studies learning outcomes that are above the KKM 79 standard.